2022
DOI: 10.1021/acsami.2c08534
|View full text |Cite
|
Sign up to set email alerts
|

Cu/CuOx In-Plane Heterostructured Nanosheet Arrays with Rich Oxygen Vacancies Enhance Nitrate Electroreduction to Ammonia

Abstract: The artificial ammonia synthesis via electrochemical nitrate reduction has met increasing research interest, but it is still necessary to develop advanced catalysts with high nitrate-to-ammonia capability. Herein, we propose and demonstrate a one-step method to construct binder-free Cu foam-supported oxygen vacancy-rich Cu/CuO x in-plane heterostructured nanosheet arrays (Cu/CuO x /CF). In addition to exposing ample active sites, the two-dimensional nanosheet morphology greatly facilitates the mass/charge-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 67 publications
(91 reference statements)
0
31
0
Order By: Relevance
“…42 Recently, some studies have shown that the introduction of oxygen vacancies in an electrocatalyst can signicantly boost its NO 3 ER activity. 25,[43][44][45][46] The main mechanism has been well recognized to be that the oxygen atoms in nitrate tend to ll the oxygen vacancies in the catalyst, which can effectively capture nitrate and promote the adsorption and reduction of nitrate, weaken the N-O bond and restrict the formation of by-products, thus improving the selectivity and efficiency of ammonia synthesis by NO 3 ER. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…42 Recently, some studies have shown that the introduction of oxygen vacancies in an electrocatalyst can signicantly boost its NO 3 ER activity. 25,[43][44][45][46] The main mechanism has been well recognized to be that the oxygen atoms in nitrate tend to ll the oxygen vacancies in the catalyst, which can effectively capture nitrate and promote the adsorption and reduction of nitrate, weaken the N-O bond and restrict the formation of by-products, thus improving the selectivity and efficiency of ammonia synthesis by NO 3 ER. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2b) shows two strong peaks at 933.2 and 953.1 eV corresponding to Cu 2p 3/2 and Cu 2p 1/2 of Cu 0 or Cu + species, while the other peaks at 935.2 and 955.3 eV (matched with the Cu 2+ 2p 3/2 and Cu 2+ 2p 1/2 ) are mainly derived from the oxidation of metallic Cu in air. 33,34 As observed in Fig. 2c, the Ti 2p spectrum of TiO 2 can be divided into two peaks centred at 458.9 and 464.7 eV, assigned to Ti 2p 3/2 and Ti 2p 1/2 , respectively.…”
mentioning
confidence: 78%
“…11a), and the 2D nanosheet arrays can offer more exposed active sites and considerably promote mass and charge transfer when combined with the 2D morphology of copper-based nanomaterials. 154 More significantly, the dual impact of heterogeneous structure and oxygen-rich vacancies enhances catalytic performance and lowers the production of byproducts. Fig.…”
Section: Other Electrocatalytic Applications Based On Copper Foam-bas...mentioning
confidence: 99%